Navigating integration and emotional distress during vulnerable stages of life - Vah Jevšnik, Mojca (Dve domovini, 2024)
Slovenia has been repatriating persons of Slovenian descent and their immediate family members from poverty-stricken Venezuela since 2019. The article explores the innate, situational, and structural vulnerabilities of the repatriates, focusing in particular on the vulnerabilities affecting their well-being and leading to emotional distress. The vulnerabilities are examined through the lens of time, i.e., before, during, and after the acquisition of the status of a repatriate, and in the context of specific age-related integration challenges. The article shows that their preferred emotional support is provided by the close-knit community of Venezuelan repatriates with whom they share the same language, culture, and experience of repatriation and integration and by the Catholic church through mass, confession, and church gatherings.
Keywords: čustvene stiske; druševno zdravje; družbena integracija; ranljivosti; repatriatriacija; Slovenija; venezuelski Slovenci